Impact of international classification of diseases, 10th revision, on head and neck surgery. (9th May 2019) - Al‐Qurayshi, Zaid; Robins, Russell; Pagedar, Nitin; Randolph, Gregory W.; Kandil, Emad
Abstract : Objectives: Review changes in the number of International Classification of Diseases, 10th Revision, Clinical Modification (ICD‐10‐CM) codes utilized in head and neck surgery service and associated changes in cost and charges of health services. Methods: A retrospective cross‐sectional analysis was performed utilizing the Nationwide Readmissions Database, 2015. The study population included patients who were admitted for a primary head and neck procedure. Patients discharged in the third quarter (Q3), coding system ICD‐9‐CM, compared to patients discharged in the fourth quarter (Q4), coding system ICD‐10‐CM. Results: A total of 11, 456 and 10, 431 patients discharged in Q3 and Q4, respectively. Comparing the top 90% billed disease codes demonstrated that the number of ICD‐10‐CM codes was more by a factor of 1.20. However, classifying codes by type of surgery, fewer codes were used in patients who had laryngeal surgeries or tonsillectomy/adenoidectomy by a factor of 0.8. Codes used to document the primary diagnoses for patients who underwent tracheostomy increased the most by a factor of 1.42. Controlling for multiple factors that would affect the cost of health services, there were no significant changes in the cost of management per case (Q3: 70, 189.00 ± 1, 546.39 vs. Q4: 70, 502.00 ± 1, 560.17, P = 0.68) or hospital charges (Q3: 273, 411.00 ± 7, 852.78 vs. Q4: 265, 996 ± 7922.77, P = 0.05). Conclusion: The ICD‐10‐CM provides an expansion of codes. Initial indication is that utilization of ICD‐10‐CM codes for head and neck surgery is within expected parameters and appears not to affect the cost of management and hospital charges despite the overall increase in ICD codes in the newer version. Level of Evidence: NA Laryngoscope, 130:398–404, 2020